3-weekly daratumumab-lenalidomide/pomalidomide-dexamethasone is highly effective in relapsed and refractory multiple myeloma. Issue 1 (1st January 2021) - Chim, Chor Sang; Kumar, Shaji; Wong, Vincent Kai Chung; Ngai, Cheong; Kwong, Yok Lam
ABSTRACT: Objectives: Myeloma relapse remains challenging. Daratumumab (dara) with immunomodulatory agents (IMiD) and dexamethasone (dex) was proven highly effective in relapsed or refractory multiple myeloma (RRMM) in randomized controlled trials. The recommended schedule of dara is weekly for eight doses, followed by 2-weekly for eight doses, and then every 4-weekly thereafter. However, the cost of daratumumab is daunting, precluding widespread and prolonged use in some countries. In this study, we aimed to evaluate the efficacy of using a 3-weekly daratumumab regimen in RRMM. Methods: Thirteen RRMM patients were treated with dara-IMiD-dex till maximal response, followed by single-agent IMiD maintenance until disease progression. Dara (every 6 weekly) would be added upon significant biochemical disease progression. Results: After a median of four daratumumab infusions (range: 3–10), the best responses included complete response (CR) in seven patients (53.8%), very good partial response (VGPR) in four patients (30.8%), and partial response (PR) in two patients (15.4%). The median time to VGPR was four weeks. At 10 months, the overall survival was 90%, and progression-free survival was 54.7%. Two of three patients tested achieved MRD-ve CR. Another patient, who had PET-CT reassessment, showed PET-ve CR. Discussion: Despite less frequent daratumumab use, we reported rapid responses with a median time to VGPR of only four weeks, and a response rate of 100% including CR rate of 54%. Despite less frequent daratumumab use, grade ¾ neutropenia remained common with a frequency comparable to that observed in Pollux. Conclusion: This 3-weekly dara-IMiD-dex regimen preserves a high efficacy with rapid, deep responses including MRD-ve and PET-ve CR, hence a cost-effective regimen.